2023
DOI: 10.1007/s12671-023-02137-0
|View full text |Cite
|
Sign up to set email alerts
|

Zoom-Based Mindfulness-Oriented Recovery Enhancement Plus Just-in-Time Mindfulness Practice Triggered by Wearable Sensors for Opioid Craving and Chronic Pain

Abstract: Objective The opioid crisis in the USA remains severe during the COVID-19 pandemic, which has reduced access to evidence-based interventions. This Stage 1 randomized controlled trial (RCT) assessed the preliminary efficacy of Zoom-based Mindfulness-Oriented Recovery Enhancement (MORE) plus Just-in-Time Adaptive Intervention (JITAI) prompts to practice mindfulness triggered by wearable sensors (MORE + JITAI). Method Opioid-treated chronic pain patients ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The results of this study are both similar and distinct from other studies to date examining the bene ts of mindfulness-based approaches as an adjunct to MOUD, and for those using or misusing prescribed opioids (Cooperman et al, 2023;Garland, et al, 2022;Garland, et al, 2023;Garland et al, 2024). The MORE and MABT interventions have overlapping components and are both focused on developing mindfulness to promote reappraisal processes that support health and well-being.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The results of this study are both similar and distinct from other studies to date examining the bene ts of mindfulness-based approaches as an adjunct to MOUD, and for those using or misusing prescribed opioids (Cooperman et al, 2023;Garland, et al, 2022;Garland, et al, 2023;Garland et al, 2024). The MORE and MABT interventions have overlapping components and are both focused on developing mindfulness to promote reappraisal processes that support health and well-being.…”
Section: Discussionsupporting
confidence: 65%
“…Prior randomized controlled trials of MBI approaches for MOUD with published outcomes involve Mindfulness-Oriented Recovery Enhancement (MORE). MORE studies have demonstrated improvements in pain, opioid use, and other outcomes in chronic pain patients receiving methadone maintenance treatment, primary care patients with opioid misuse, and people with chronic pain on prescribed opioids (Cooperman et al, 2023;Garland et al, 2022;Garland et al, 2023;Garland et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…This could include wearable sensors, along with various digital inputs captured through smartphones and other devices, such as audio and visual data, text from email and other messaging platforms. Garland et al (2023) exemplified this approach by leveraging heart rate variability measured via wearable sensors to tailor the delivery of mindfulness practices. Additional potential examples include prompting individuals to engage in mindful walking when walking is detected through the Global Positioning System (GPS) or encouraging intentional feelings of loving-kindness and compassion when their use of social media to interact with others is identified.…”
Section: The Moment Is Now: Future Directions For Mb-emismentioning
confidence: 99%
“…In a recent RCT,Garland et al (2023) explored the efficacy of combining Zoom-based Mindfulness-Oriented Recovery Enhancement (MORE) with EMI prompts triggered by wearable sensors in opioid-treated chronic pain patients. The study randomized participants (n = 63) into either MORE + EMI or a Zoom-based supportive group psychotherapy control.…”
mentioning
confidence: 99%